A gas-phase “top-down” chemical link between aldehydes and alcohols - Shingledecker, Christopher N.; Molpeceres, Germán; Flowers, A. Mackenzie; Warren, Deaton; Stanley, Emma; Remijan, Anthony (Frontiers in Astronomy and Space Sciences, 2026)
IntroductionAlcohols and aldehydes represent two key classes of interstellar complex organic molecules (COMs). This work seeks to better understand their possible chemical connections, with a focus on such molecules in the sources of the star-forming region Sgr B2 (N).MethodsThe gas-phase reaction between ethanol (CH3CH2OH) and the halogens fluorine and chlorine was investigated via DFT calculations, with the goal of determining whether astrochemically viable chemical pathways leading to acetaldehyde (CH3CHO) exist. The studied reactions were then included in an astrochemical model of Sgr B2 (N) to determine their significance under real interstellar conditions.ResultsOur DFT calculations revealed that both chlorine and fluorine can react barrierlessly with ethanol to abstract a hydrogen atom. We further found that, following this initial step, the resulting ethanol radicals can undergo further reactions with atomic hydrogen, with some routes leading to acetaldehyde. Incorporation of these novel reactions in astrochemical models of hot cores suggest that they are indeed efficient under those conditions, and can lead to modest increases in the abundance of CH3CHO during model times where gas-phase ethanol is abundant. Of the ethanol radicals included in our chemical network, we found CH3CHOH to have the highest abundances in our simulations comparable to that of ethanol at some model times.DiscussionOverall, this work reveals a novel gas-phase “top-down” link from alcohols to aldehydes that compliments the better studied “bottom-up” routes involving grain-surface H-addition reactions yielding alcohols from aldehydes. Moreover, results from our astrochemical models suggest that the ethanol radical CH3CHOH may be detectable in the interstellar medium.